Analysis of building in Ricardo Palma’s «Las tres puertas de San Pedro» - Tintaya Sánchez, Sebastian André (2021)
This article will analyse, from the perspective of both Civil Engineering and Architecture, the story of «Las tres puertas de San Pedro» by our beloved Ricardo Palma, who in this text relates the creation of this church and how they managed to build its third door without being a cathedral. Therefore, I will identify the features and structural bases of Civil Engineering and also mention Architecture, as both careers are related to each other; this is demonstrated in the accounts of their identification, location, restructuring and building and facade licences.